Suspended solid removal efficiency of plate settlers and tube settlers analysed by CFD modelling - W. M. L. K. Abeyratne; S. B. Weerakoon; Panduka Neluwala; Harsha Ratnaweera (Water Science and Technology, 2023)
Removal of suspended solids from raw water is an essential process in water treatment plants. Conventional sedimentation tanks in water treatment plants occupy a large area and become expensive in urban areas. The use of plate settlers or tube settlers in sedimentation tanks to increase the efficiency and hence reduce the footprint of sedimentation tanks is an economical solution in water treatment. This study investigated the effectiveness of plate and tube settlers compared to conventional settlers in a water treatment plant. A three-dimensional Computational Fluid Dynamics (CFD) model was set up using ANSYS-CFX 17.2. Seven cases (a conventional settler, three plate settlers and three tube settlers) were analysed to compare the settler performances. The maximum removal efficiencies of all solid classes were approximately equal in plate and tube settlers with the same plate spacing and tube depth: around 100%, 67%, 28% and 9% for the solid classes with particle diameters of 41, 17, 9.5 and 5.0 µm, respectively. The settling efficiency remained unchanged with the increase of the plate settling area beyond 60% of the conventional settler area under the given tank and flow conditions. The tube cross-section shape does not affect the particle removal efficiency of a tube settler. HIGHLIGHTS Plate settlers and tube settlers are increasingly used to reduce the water treatment plant footprint with the increasing land prices in urban areas.; The present study compares the efficiency of these settlers in the removal of suspended solids of different size classes by three-dimensional computational modelling using ANSYS CFX.; The model developed here can be used to upgrade existing conventional settling tanks paying due attention to the removal efficiency of different solid classes.;